Tumors of the orbit and periorbital region: 20-year experience of the N.N. Blokhin National Medical Research Center of Oncology - T. R. Andreev; M. A. Kropotov; R. I. Azizyan; A. M. Mudunov; V. Z. Dobrokhotova (Опухоли головы и шеи)
Introduction. Neoplasms of the orbit and periorbital region are usually represented by tumors of the eyelid skin  skin of the periorbital region  and paranasal mucosa. The most common histological types of this pathology are squamous cell and basal cell carcinomas. The main indications for orbital exenteration are tumor lesions in the extraocular muscles and orbital apex and irreversible vision loss in the affected eye at the time of surgery planning. In the absence of these pathologies  organ-sparing surgery is recommended. Resection of orbital and periorbital tumors (including orbital exenteration) leads to cosmetic and functional defects  therefore surgical treatment of this area should be performed only if other methods are impossible or ineffective.Aim. To analyze the experience of resection of orbital and periorbital tumors and to evaluate short- and long-term results of surgical treatment of this pathology.Materials and methods. Retrospective analysis of patients with tumors of the orbit and periorbital region who underwent organ-sparing and exenteration surgeries between 2003 and 2023 was performed.Results. Overall 5-year survival was 55 %. It varied depending on a number of factors. The best 5-year survival rates were observed for basal cell carcinoma of the eyelid skin and periorbital region (83 %)  the worst for squamous cell carcinoma (34 %) and melanoma (41 %). For localized tumors (Т1)  overall survival was 76 %  for locally advanced (Т4) – 43 %.Conclusion. Orbital and periorbital neoplasms are characterized by a variety of tumor morphological types and locations which requires multidisciplinary approach to treatment and rehabilitation of patients with this pathology.